Pengembangan Model Desain Pembelajaran Daring Berbasis Teknologi Informasi dan Komunikasi di Era Budaya Digital Sekolah Dasar - Magdalena, Ina; Jannati, Ahmad Rafaeli; Munaroh, Wardatul (MASALIQ, 2023)
The research conducted is a type of technology development research for learning in elementary school children. First conduct a survey on the use of online learning based on information and communication technology in the era of digital culture, the use of online applications by learners. In the development stage, the development of learning tools is carried out which includes making blogs or webs and also online applications, developing learning modules. conduct an assessment or survey of online applications controlled by teachers. The application was agreed by the teachers as a whole. From the results that have been obtained that the application used is more familiar with the Google classroom site which is linked to the teacher's web or blog and the learning model formed blended learning with problem-based learning strategies, or also with applications as a forum for communication using Whats App, sms, messenger, telephone, and e-mail and zoom or meet. the application of online learning, the focus of technology can be in the form of training for teachers, in addition to students or parents of students, both in the use of learning management systems monitoring and conducting online evaluations, virtual work. that the online learning model in the era of digital culture, the use of online applications as a means of collaborating and communicating which in this case is used online applications can be concluded that the model is an exciting learning model for students and students.